A Friendly Response to the Friendly Reviewers and Critics - Havelka, Miloš (Dějiny – teorie – kritika, 2007)
Miloš Havelka responds above all the the criticisms from Martin Putna and argues that his starting point for the study of the genesis of the dispute on the meaning of Czech history was not meta-ideological but based on the sociology of knowledge. He also gives the reasons why he did not include in the anthology texts replicating Kundera's essay of 1969, The Czech Fate, and why he also did not include texts reflecting the Marxist, primarily Nejedlý's. Reacting to Putna's criticisms relating to the unrepresentative character of the texts by Catholic authors, Havelka defends his choice and refers to the preface to the anthology, which explains in detail why he did not include texts by Zdeněk Kalista and Bohdan Chudoba.